SCIENTIFIC PUBLICATION TRENDS IN GREEN EDUCATION AND DIGITAL SUSTAINABILITY: A BIBLIOMETRIC ANALYSIS - Evcimik, Sare; Gokcen, Elvan; Alpsulun, Mustafa; Barut, Muzeyyen; Akpinar, Esra Nur; Balikci, Hasan Celal (Escola Superior Dom Helder Camara, 2025)
This study examines research trends, conceptual development, and thematic evolution in green education and digital sustainability using bibliometric methods. 438 articles from the Education & Educational Research category of the Web of Science (WoS) Core Collection, covering the period 1990-2025, were analyzed. The findings indicate that the green education literature expanded rapidly, particularly after 2005, and that digital sustainability themes gained prominence after 2015, influenced by SDG 4.7. The countries with the most publications were the United Kingdom, Spain, China, and the United States, while Turkey's contribution after 2018 was notable. The keyword and temporal analysis revealed that the literature evolved from environmental awareness to digital sustainability pedagogy, and that green education has evolved into a multidimensional structure encompassing digital ethics, technological responsibility, and sustainable pedagogy.
Keywords: Green Education; Sustainable Pedagogy; Sustainable Development Goal 4.7. Bibliometric Analysis; Digital Sustainability